The Impact of Ai-Driven Live Shopping and Experience Value on Repurchase Intention on Shopee - Burhan Irsad Said; R Hidayat (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the influence of AI-Driven Live Shopping and Experience Value on Repurchase Intention among Shopee users in Indonesia. As digital technology advances, the integration of artificial intelligence into live shopping features has become an increasingly vital marketing strategy to attract consumers and foster loyalty. A quantitative approach was employed using a survey method, where questionnaires were distributed to 385 respondents who are active Shopee users and have watched Shopee Live. The collected data were analyzed using descriptive statistics and multiple linear regression. The findings indicate that AI-Driven Live Shopping significantly influences Experience Value, and Experience Value, in turn, significantly affects Repurchase Intention. This research highlights the critical role of consumer experience in bridging technology with repeated purchase behavior and provides strategic insights for e-commerce platforms to enhance digital engagement and strengthen long-term customer loyalty.